Illegality and the civil law in Singapore: Lessons from the UK? Patel v Mirza [2016] 3 WLR 399; [2016] UKSC 42 - ONG, Benjamin Joshua (Institutional Knowledge at Singapore Management University, 2017)
The law on the illegality defence in Singapore is in a fragmented state. In Patel v Mirza, the UK Supreme Court attempted to overhaul this notoriously confusing area of the law, and presented various ideas which are of potential interest to its development in Singapore.